Jabatan Kerja Raya Daerah Muar / Muhammad Ismail Sukhata - Sukhata, Muhammad Ismail (Faculty of Civil Engineering, 2018)
The main purpose Industrial Training (IT) is required for students is to provide work experience and knowledge that is more widely in their chosen field so that students are more willing to work in the future. It is a chance for us to use everything that we have learned at university to work in the kind of real-life situations that we will face when we start our career. First of all, this report is about my industrial training that I have been going through for two month, which is 8 weeks. The place where I having my industrial training is at Jabatan Kerja Raya (JKR) Daerah Muar. I choose this place as my location for industrial training is because JKR is the federal government department in Malaysia which is responsible for construction and maintenance of public infrastructure in Malaysia. So, I think I will learn a lot of things at this company. The company also is near to my home town as well. The reason I choose to do my internship locally because I believe that I will gain a lot of experiences which I have yet to explore whether it is related my course or anything that related to real life as an engineer. This internship is a great experience for me to learn and improve as well as to develop my skills in engineering field. Next, my experience in JKR Muar have teach me how is the environment work and working attitude in an organization . This report consist of four chapters that are introduction, training attended, technical report and conclusion. For the first chapter which is introduction I will tell about my company background, organization charts and nature of business in this company. Then for the chapter two consist of weekly summary based on my logbook that I have write daily. In chapter three, it is about a technical report and I will share about the project that I have investigate at JKR . All about the test on the site, documents and more also have been explained in this report. Lastly, chapter four is about what I have gained throughout my industrial training. That all I can share about my report and I hope all information in this report will make benefit to all engineering students.